Crusading and matrimony in the dynastic policies of Montferrat and Savoy - Barker, John W. (Byzantion Nea Hellás, 2017)
The uses of matrimony have always been standard practices for dynastic advancement through the ages. A perfect case study involves two important Italian families whose machinations had local implications and widespread international extensions. Their competitions are given particular point by the fact that one of the two families, the House of Savoy, was destined to become the dynasty around which the Modern State of Italy was created. This essay is, in part, a study in dynastic genealogies. But it is also a reminder of the wide impact of the crusading movements, beyond military operations and the creation of ephemeral Latin States in the Holy Land.